A thorough scrutiny of ELT textbook evaluations: a review inquiry - Gholami, Reza; Noordin, Nooreen; Rafik-Galea, Shameem (Australian International Academic Centre, 2017)
It is thoroughly agreed that English language textbooks stand amongst the foremost components in any language classrooms worldwide, being referred to as valid, beneficial and labor-saving tools to fulfill an extensive range of needs. An ELT textbook is not merely a set of sheets of paper fastened together to hinge at one side, but is the beating heart of any education system whereupon the whole learning revolves. Notwithstanding their interminable benefits, it is admitted that still the compiled textbooks, especially the ones prescribed in Educational systems have to be evaluated and assessed to confirm whether they fulfill the objectives they are meant for or not, as it is said no perfect textbook exists. Having dealt with evaluation in general, this research meticulously elaborates on textbook evaluation more specifically concluding that there is a dearth of inquiry on textbook selection and evaluation. Afterwards, this research introduces the most common approaches for evaluating ELT textbooks and materials. The paper culminates with concluding remarks and implications, hoping to shed light on how textbook evaluation is practiced worldwide.